Anastomosis between the transverse cervical nerve and marginal mandibular nerve: how often does it occur?. Issue 3 (April 2017) - Brennan, P.A.; Elhamshary, A.S.; Alam, P.; Anand, R.; Ammar, M.
Abstract: Anastomoses in the neck between the sensory transverse cervical nerve (C2, 3) and the cervical branch of the facial nerve are common, but communications with more superior branches of the facial nerve are rare. After we had identified a case where the transverse cervical nerve joined the marginal mandibular branch of the facial nerve in the submandibular triangle during a selective neck dissection, we searched for this variant in 86 neck dissections to see if it occurs more often than expected. We found it in one further patient. As this anastomosis of the nerve could easily be confused with the marginal mandibular branch itself, particularly during a more limited exposure (such as excision of a submandibular gland), our findings remind surgeons to be vigilant when dissecting in this area to minimise the risk of weakness of the lower lip postoperatively.